Implementation of indonesian teacher learning processes and digital literation for teachers in junior high school - Ahmad Basori; Dessy Wardiah; Yessi Fitriani (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This is to determine the effect of work motivation and principal leadership together on the performance of teachers in SD Negeri Lengkiti District. In this study, quantitative research methods were used and the research design was in the form of an influence study, namely to determine the effect of the three variables, namely the independent or independent variable Teacher Motivation (X1), Principal Leadership (X2) and the dependent or dependent variable Teacher Performance (Y). The results of the study can be concluded as follows: 1) The variable of work motivation of the SD Negeri Lengkiti District teachers is in the sufficient category, 2) The leadership variable of the principal of SD Negeri Lengkiti District is in the good category, 3) The work motivation of the teacher and the leadership of the principal is factors that can improve teacher performance.